Internalized Misogyny: Oppression Among Women In Lady J Movie By Emmanuel Moret - Resha Naura Safa Amelia; Wening Udasmoro (Universitas Muhammadiyah Semarang, 2023)
The endless oppression of patriarchy creates competition in women's relationships. Women observe, defeat, insult, belittle, and overthrow each other, which is included in the acts of internalized misogyny. Internalized misogyny is a tool used by patriarchy to keep women as subordinate by diverting women's attention from opposing patriarchy to fighting among themselves. Internalized misogyny strengthens the oppression of women in society. Women evaluate other women from their behavior, physical appearance, and even their private lives. Discriminatory acts such as mockery, bullying, labeling, decreasing women's value, and exploitation of women's rights unknowingly also have been committed by women. Thus, the main focus of this paper is to reveal how internalized misogyny occurs in the process of women’s opposition to patriarchy that is included in a movie entitled Lady J. This movie shows that unknowingly for women, in an attempt to defeat patriarchy, women sacrificed other women. The movie narrates a story of a Marquise who is a female aristocrat in France who intends to take revenge on her ex-husband by working with a family of prostitutes. The aim of this paper is to examine internalized misogyny depicted in Lady J movie and to criticize the movies containing internalized misogyny acts that tend to be unrealized or even normalized. This research uses theories of misogyny, bad women, and silencing by Kate Manne and the relations of the patriarchal system and the internalization of discrimination by Sheryl Sandberg. This research uses data collection and analysis methods that reveal the action of internalized misogyny that occurs in the relationship between female figures and their resistances.